Application of Resource-Based Learning Model to Increase Motivation for Social Studies Learning on Cooperative Materials in Class IV SDN Sukaraya 03 - Jaya, Aris; Syaodih, Ernawulan (International Conference on Elementary Education, 2021)
This research is motivated by the low learning motivation of students in social studies subjects in grade IV SD Negeri Sukaraya 03. This study aims to find out and get an overview of Improving Social Studies Learning Motivation on Cooperative Materials in Class IV SDN Sukaraya 03 Kabufaten Bekasi and to find out whether there are benefits of Resources -Based learning on the quality of the social studies learning process in elementary schools. The benefit of the research results can provide some information about the practice of social studies learning patterns in cooperative materials through the Resource-Based Learning Model that teachers should do. The results of the study showed significant progress and improvement in each cycle. Resource-Based Learning can increase the motivation of the learning process which spurs students to be more active, creative, and innovative in learning.